Implementation of Islamic Religious Education in Building Religious Values for Elementary School Students IT Al Istiqomah Puri Kosambi Karawang - Irwanto Firmansyah; Amirudin; Achmad Junaedi Sitika (GoAcademica Research & Publishing, 2021)
To form human beings who are religious and have religious values ​​in themselves, directed education is needed. An educational institution should introduce and instill monotheism or faith to students as the initial foundation before students get to know many other disciplines. Therefore, the purpose of this study was to determine the process of implementing Islamic religious education in building religious values ​​for students at SD IT Al Istiqamah Puri Kosambi Karawang. This research is field research using a qualitative descriptive approach. The results of this study indicate that the implementation of Islamic religious education in building religious values ​​in the SD IT Al Istiqamah Puri Kosambi environment is carried out well and effectively by applying it in daily activities such as getting used to saying greetings, shaking hands, polite in speaking, polite in attitude, and mutual respect both with teachers and fellow friends. In addition, intra-curricular learning activities are also carried out centered on students and maximized on aspects of conceptual and illustration material and contextual examples.